Factors influencing dietary patterns among the youth from higher educational institutions in India - Soam, Sudhir K.; Yashavanth, B. S.; Dhumantarao, Thammi Raju; Maruthamuthu, Balakrishnan; Balasani, Raghupathi; Rakesh, S. (Frontiers in Nutrition, 2023)
Purpose To determine the factors influencing the dietary habits of the varied groups among adults in India. Design/approach Data on food habits such as choice of diet, preference toward meat, spicy food, sugar/calorie etc., were collected from the participants (from several higher education institutions) of different training programmes and events organised at ICAR-NAARM, Hyderabad and its students of Post Graduate Diploma in Agribusiness Management. Findings Results of the study indicated that the food choice of the respondents is highly influenced by their region, age and gender. Most of the respondents preferred vegetarian food with increasing age. We also noticed that as age of the respondents increased, their preference toward simple & plain food (with less oil/spice) also increased. From the present investigation, it is recommended that the customized food menu should be prepared in every food serving institution based on the region, age and gender of the consumer. Novelty Analysis of dietary patterns can be helpful for doctors, dieticians, food policy-making, restaurateurs, youth hostels, food organisations, mega kitchens etc. that would also contribute to responsible food consumption.